2017
DOI: 10.23910/ijbsm/2017.8.5.1848b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc on Growth, Plant Yield, NPK Uptake and Economics

Abstract: The experiment was conducted at agricultural farm of Palli Siksha Bhavana, Visva-Bharati at Sriniketan of Birbhum district, West Bengal during pre-rabi season of 2015 to study the effect of zinc on growth and productivity of baby corn. The soil at experimental site was analysed sandy loam in texture with low in available N, medium in available P 2 O 5 and K 2 O and slightly acidic (p H : 4.78) in nature. The experiment was carried out in RBD with 8 treatments. Each treatment was replicated thrice and the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
3
2
0
Order By: Relevance
“…High dry matter in those treatments is due to long plant height, high stem girth, and high root weights. These findings are in the harmony with those obtained by Marngar and Dawson [10] and Palai et al [11].…”
Section: Plant Dry Weight (G/plant)supporting
confidence: 92%
“…High dry matter in those treatments is due to long plant height, high stem girth, and high root weights. These findings are in the harmony with those obtained by Marngar and Dawson [10] and Palai et al [11].…”
Section: Plant Dry Weight (G/plant)supporting
confidence: 92%
“…Long plant height, large stem girth, and heavy roots cause the treatments' high dry matter. These findings are in harmony with those obtained by Palai et al [8].…”
Section: Plant Dry Weight (G/plant)supporting
confidence: 93%
“…Soil application of zinc sulphate @ 37.5 kgha -1 with 0.5% foliar spray at 20 and 40 DAS recorded a higher NAR with an increment of 14.7% and 28.2% between 25 DAS and 45 DAS and between 45 DAS and harvest stages, respectively. The experimental results are in accordance with the findings of Palai et al (2017) who reported that the higher rate of zinc applied as seed priming and foliar spray @ 2% gave maximum NAR.…”
Section: Effect Of Zinc Fertilization On Physiological Parameters Of Babycornsupporting
confidence: 91%
“…It is obvious because of the favourable effect of zinc application on production of higher babycorn and green fodder yield as well as remunerative returns in spite of higher cost of cultivation. Palai et al (2018) found that the highest net return ( �165442 ha -1 ) was observed with soil application of Zn @ 6 kgha -1 along with foliar spray @ 0.05% Zn at 25 DAS with seed treatment @ 0.6% Zn. The B:C ratio was also highest (4.46) in soil application of Zn @ 6 kgha -1 along with foliar spray @ 0.05% Zn at 25 DAS.…”
Section: Effect Of Zinc Fertilization On Economics Of Babycornmentioning
confidence: 93%